Book Review: Asia Tenggara Masa Modern Awal - NFN Jamaluddin (Jurnal Lektur Keagamaan, 2015)
A book written by Reid, Charting the Shape of Early Modern Southeast Asia, examines the period of the early stages of modern history of Southeast Asia from the 15th century until the 17th century. The issues raised are trade and capitalism in Southeast Asia. In this book, Reid uses "Early Modern" asa basic concept. This book discusses several key issues, one of them is the trade route through certain trade cities in Southeast Asia has more portion of discussion and more themes are also disscused, although the explanation isdenser and shorter. The approach used in this book is Annales approach. Reid wants to totally present the events of the early modern history of Southeast Asia. Therefore serious efforts are made to enrich the resources used. Reid is able to access a variety of sources, be it of the results of the study of anthropologists, sociologists, modern geographers, and the works of traditional historians presented to raise the most vital historical dimensions of people in Southeast Asia that have been neglected. The superiority of this book is Reid’s success to uncover the important information contained in thechronicles which is an important work produced by the local community in Southeast Asia. Reid also uses the results of the philologists’ studies to write the history of Southeast Asia.